Pengaruh Metode Pembelajaran Problem Based Learning Terhadap Hasil Belajar Fisika Ditinjau Dari Kemampuan Dasar Matematika Siswa Kelas X SMA Tulus Bhakti Jati Asih Bekasi - Wati, Sartika Lisna (Jurnal Gemaedu, 2018)
The purpose of this study is to examine the effect of the interaction of learning-based learning method to physics learning outcomes in the review of mastery of basic mathematical skills. This research was conducted at SMAS Jati Asih Bekasi with the sample of 130 students. The method used is the experimental method with design treatment by level factorial 2 x 2 and using a quantitative approach. Instruments used to measure physics learning outcomes and basic mathematical skills are used multiple choice questions. Calculation of quantitative data analysis is done using Two Path Analysis. Based on the results of the analysis can be concluded that learning using Problem Based Learning model can improve physics learning outcomes and basic math skills better when compared with improvements in classes that use conventional learning.